The Relationship between Conditioning Regimen with Viral and Fungal Infections in Allogeneic Hematopoietic Stem Cell Transplantation - Merve, Pamukcuoglu (Journal of Hematology Research, 2021)
Background: Infections are one of the most important factors that adversely affect the transplantation process at hematopoietic stem cell transplantation (HSCT). Quality of life and even the loss of patients due to infection may result in the failure of the HSCT. While the studies in the literature were mostly related to bacterial infections in HSCT, the viral and fungal infections were evaluated. The relationship between viral and fungal infections and the types of conditioning regimens used in HSCT was investigated. Methods: Three hundred fifthy one (351) patients who had allogeneic HSCT were performed. The viral and / or fungal infections and conditioning regimens were determined from the medical records. The conditioning regimens were evaluated in two groups as myeloablative and non-myeloablative. We aimed to determine the statistical relationship between viral and fungal infections and type of conditioning regimen. Results: Of the 351 patients, 104 had CMV infection, 4 had parvovirus infection, and 87 had fungal infection. Myeloablative regimen was used in 226 of 351 patients and non-myeloablative regimen was used in 125 patients. There was no significant relationship between the type of conditioning regimen and CMV, parvovirus and fungal infections. Conclusion: The lack of a significant relationship between the type of conditioning regimen and the viral and fungal infections during HSCT provides the clinician with the choice of the conditioning regimen. However; we need to do more studies with larger case series and also relationship between the type of conditioning regimen and viral and fungal infections should be more clearly demonstrated.